Edge Computing Paradigms for Real-time Media Applications: Optimizing Latency, Bandwidth, and Scalability - Srikar kompella (International Journal of Computational and Experimental Science and Engineering, 2025)
Edge computing represents a transformative paradigm shift for real-time media applications, fundamentally altering how processing resources are distributed across network infrastructures. This article examines the evolution from centralized cloud architectures to distributed edge computing models, addressing critical challenges in latency reduction, bandwidth optimization, and scalability for media-intensive applications. Through distributed processing topologies, edge-cloud integration frameworks, and data flow optimization techniques, we present quantitative performance improvements achieved through edge deployment. The article explores latency reduction methodologies, intelligent data distribution strategies, and scalability solutions that collectively enhance media delivery across diverse application domains. Case studies in live event broadcasting, video conferencing, smart surveillance, and telehealth demonstrate the practical benefits of edge-based media processing. Looking forward, we examine emerging trends including integration with next-generation networks, AI-enhanced media optimization, standardization efforts, and specialized hardware accelerators that will shape the future landscape of edge computing for real-time media applications.